Privacy Protection in the Big Data Era: A Review of Personal Data Protection Policies - Zainul Djumadin (Jurnal Restorasi : Hukum dan Politik, 2023)
In the face of the rapid development of Big Data, privacy protection has become a central issue that requires serious attention. This research aims to conduct a comprehensive review of existing personal data protection policies, with a focus on their relevance in the context of the Big Data era. We analyze the impact of large-scale data collection, processing and analysis on individual privacy, and evaluate the extent to which current data protection policies can address emerging challenges. This research uses a qualitative approach with descriptive methods. The research results show that personal data protection has become a major concern in Indonesia, especially due to the increase in data breaches and leaks. Although there have been efforts by the government and the DPR to draft a special draft law (RUU), the bill has not yet been passed into law. An important point in the bill is the application of the principle of extra-territorial jurisdiction, which emphasizes data protection obligations for all entities, both within and outside Indonesian jurisdiction. Although the bill is still awaiting approval, this step reflects the government's determination to create a solid legal foundation that is responsive to the complex challenges of personal data protection in the digital era.